Human resource development and training in the digital transformation era - Doni Febrian Ashadimas (Curricula: Journal of Curriculum Development, 2025)
Digital transformation has significantly reshaped the paradigm of Human Resource Management (HRM), compelling organizations to adapt their training methods, work structures, and managerial strategies to remain competitive in the technological era. This study aims to analyze the dynamics of digitalization in HRM, focusing on four main aspects: the impact on training and education, challenges faced, emerging opportunities, and strategic responses that HRM can adopt. The research employs a Systematic Literature Review (SLR) method, involving the stages of identification, screening, eligibility assessment, and study inclusion. Data were collected from academic databases, Watase UAKE, and Scite, using keywords relevant to HRM in the digital era. After applying inclusion and exclusion criteria, ten relevant articles were selected for in-depth analysis. The synthesis process was conducted through a full-text reading and thematic coding approach. The findings reveal that digitalization has a positive impact, increasing work efficiency, enabling data-driven decision-making, and expanding flexibility in work systems and training methods. In conclusion, digitalization in HRM brings significant changes to training practices, organizational structures, and strategic planning by promoting the adoption of technology that fosters both efficiency and innovation.   Abstrak Transformasi digital telah mengubah paradigma pengelolaan sumber daya manusia (SDM), menuntut organisasi untuk menyesuaikan metode pelatihan, struktur kerja, dan strategi manajerial agar tetap kompetitif di era teknologi. Penelitian ini bertujuan untuk menganalisis dinamika digitalisasi dalam pengelolaan SDM, dengan fokus pada empat aspek utama: dampak terhadap pelatihan dan pendidikan, tantangan yang dihadapi, peluang yang tersedia, serta strategi yang dapat diterapkan oleh MSDM. Penelitian ini menggunakan metode Systematic Literature Review (SLR) dengan tahapan identifikasi, skrining, evaluasi kelayakan, dan inklusi studi. Data dikumpulkan dari basis data Watase UAKE dan Scite, dengan kata kunci yang relevan terhadap pengelolaan SDM di era digital. Setelah melalui proses seleksi berbasis kriteria inklusi dan eksklusi, diperoleh 10 artikel yang dianalisis secara mendalam. Proses sintesis dilakukan melalui pembacaan penuh dan pengkodean tematik. Hasil penelitian menunjukkan bahwa digitalisasi membawa dampak positif dalam bentuk peningkatan efisiensi proses kerja, pengambilan keputusan berbasis data, serta perluasan fleksibilitas dalam sistem kerja dan pelatihan. Kesimpulannya, digitalisasi dalam pengelolaan SDM membawa dampak signifikan terhadap transformasi pelatihan, struktur kerja, serta strategi organisasi melalui adopsi teknologi yang mendorong efisiensi dan inovasi. Kata Kunci: industri 4.0; pelatihan; pendidikan; pengelolaan SDM; transformasi digital